Pengetahuan Arkeologi sebagai Muatan Lokal: Penerapannya di Maluku - Marlon NR Ririmasse (Balai Arkeologi Maluku, 2014)
Diversity is essentially an element that unites Indonesia. The broad geographical character of the region and the complexity of its cultural profile has established a nation with such a colorful appearance. An ability to manage this major diversity has become an absolute requirement as a country. The sensitivity to identify any specific needs of each element of the nation would always be an aspect that must be reviewed and reshaped periodically. Which is also included the need in the education sphere. Local content may be considered as a national solution to answer the breadth dimension of necessity in the school level for the teaching materials that linked with the local characteristics. Connected to this aspect is the interest to provide the knowledge of local culture. Archaeology is a discipline that adequate to share this strategic role for public. This article tries to discuss the contribution of the archaeological study in the development of local content in Moluccas. Literature study have been chosen as an approach to collect data. This study found that archaeology is potential to be developed as a part of local content material in Moluccas.Keberagaman sejatinya adalah elemen yang menyatukan Indonesia. Bentang luas geografis dan wajah kompleks budaya nusantara telah membentuk suatu bangsa dengan warna yang begitu raya. Maka kemampuan untuk mengelola kebhinekaan menjadi syarat mutlak yang harus dimiliki sebagai negara. Kepekaan untuk menemukenali kebutuhan-kebutuhan spesifik setiap elemen bangsa kiranya menjadi aspek yang senantiasa harus ditinjau dan dibentuk kembali. Termasuk kebutuhan dalam ranah pendidikan. Muatan lokal pada hakekatnya merupakan solusi nasional dalam menjawab luasnya dimensi kebutuhan di tingkat sekolah akan materi yang bertautan dengan karakteristik daerah. Melekat dalam hal ini adalah kebutuhan untuk menyajikan pengetahuan budaya lokal. Arkeologi juga menjadi bidang yang dituntut berbagi peran dimaksud. Tulisan ini mencoba untuk mendiskusikan kontribusi studi arkeologi dalam pengembangan muatan lokal di Maluku. Studi pustaka dipilih sebagai pendekatan dalam pengumpulan data. Kajian ini menemukan bahwa arkeologi dan pengetahuan sejarah budaya potensial untuk dikembangkan sebagai bagian dari materi muatan lokal di Maluku.